Low-conductivity high-reflection glaze for photovoltaic glass back plate of double-glass assembly and application method of low-conductivity high-reflection glaze
By applying a specific formula of low-conductivity and high-reflection glaze on the photovoltaic glass back plate, the problem of glass prone to black spots in the PID test in the prior art is solved, and the high reflectivity and low conductivity are achieved, ensuring the performance and appearance requirements of the photovoltaic glass back plate.
Patent Information
- Application Number
- CN202411672722.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-07
AI Technical Summary
The existing high-reflection coating technology can easily cause dark spots in the glass during the PID-resistant testing process, affecting the appearance and technology promotion of the photovoltaic glass back panel.
A low conductivity and high reflective glaze is used, and its raw material formula includes modified rutile, glass binder, quartz fuse, nanozirconium silicate, ink oil and diluent. It is coated on the photovoltaic ultra-white glass back plate by screen printing and baked at a temperature of 680-720°C.
High reflectivity (visible light reflectivity > 80%) and low conductivity (conductivity ≤1×10-4) are achieved, while avoiding dark spots in glass, ensuring the appearance and performance requirements of the photovoltaic glass back panel.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glass glazes, and in particular to a low-conductivity, high-reflection glaze for a double-glass module photovoltaic glass back plate and an application method thereof. Background Art
[0002] High-reflective glaze refers to glass or other carriers coated with high-reflective glaze under sunlight, which can highly reflect visible light, solar infrared and ultraviolet rays in the range of 400 to 2500nm, thereby increasing the reflection intensity.
[0003] Solar photovoltaic cells are semiconductor devices with photoelectric conversion characteristics. They directly convert solar radiation into direct current. Solar cell modules (also called solar panels) are the core and most important part of solar power generation systems. Their function is to convert solar energy into electrical energy, or to store it in batteries, or to drive loads. In order to improve the efficiency of photoelectric conversion, double-glass photovoltaic cell modules have been developed in recent years. They are composed of two sheets of glass (front glass, back glass) and solar cells to form a composite layer. The cells are connected in series and parallel to the lead ends to form a photovoltaic cell module. The back glass is coated with a white high-reflection coating so that the visible light from the sun that passes through the glass is reflected back onto the cells.
[0004] However, currently, the existing high-reflective coating technologies all have the problem of black spots on the glass during the anti-PID test, which affects the appearance requirements of the photovoltaic glass backplane and has an impact on the technology promotion of the double-glass photovoltaic cell module industry. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a low-conductivity, high-reflection glaze for a double-glass module photovoltaic glass backplane, which has simple process, low cost and is easy to use, and an application method thereof.
[0006] The present invention is achieved through the following technical scheme: a low-conductivity, high-reflection glaze for a double-glass module photovoltaic glass back panel, characterized in that the raw material formula of the low-conductivity, high-reflection glaze is composed of the following weight percentages: modified rutile 35-50wt%, glass binder 30-45wt%, quartz frit 10-20wt%, nano zirconium silicate 1-5wt%, additional varnish 18-24wt%, and diluent 1-3%.
[0007] The particle size of the low-conductivity and high-reflection glaze raw material is less than 8 μm.
[0008] The modified rutile is rutile titanium dioxide with 20wt%Al 2 O 3 Aluminum sol and 20 wt % SiO2 It is made by wrapping with silica sol.
[0009] The chemical composition of the glass binder is Sb 2 O 3 0~5wt%Na 2 O 7~10wt%, K 2 O 2~5wt%, ZnO3~22wt%, B 2 O 3 16~35wt%,SiO 2 15~35wt%,TiO 2 3~5wt%,Al 2 O 3 1~3wt%,BaO 2~11wt%,MgO 0~2wt%, SrO 0~11wt%CaO 0~11wt%.
[0010] The particle size of the nano zirconium silicate is 400-600nm.
[0011] The varnish is composed of 3 wt % of polycaprolactone, 3 wt % of acrylic resin, 40 wt % of dipropylene glycol monomethyl ether, 53 wt % of tripropylene glycol monomethyl ether, 0.5 wt % of defoaming agent and 0.5 wt % of leveling agent in weight percentage.
[0012] The weight percentage composition of the diluent is: 1 wt % of water-based acrylic resin, 0.5 wt % of polycaprolactone, 0.5 wt % of fumed silica, and 98 wt % of diethylene glycol butyl ether.
[0013] The application method of the above-mentioned low-conductivity and high-reflection glaze is characterized in that: the low-conductivity and high-reflection glaze is coated on the surface of the photovoltaic ultra-white glass backplane by screen printing, and baked at a temperature of 680-720°C for 90-135s to obtain a low-conductivity and high-reflection double-glass module photovoltaic glass backplane.
[0014] The coating thickness of the low-conductivity high-reflection glaze is 15-24 μm.
[0015] The low conductivity and high reflection double glass photovoltaic glass back panel has a visible light reflectivity of 82.18-83.62% and a conductivity (700°C) of 0.32×10 -4 ~1×10 -4 s / m, pencil hardness is 9H.
[0016] The present invention has the following beneficial effects: (1) The low conductivity and high reflective glaze of the present invention is firmly bonded to the glass, has good adhesion performance, is not easy to scratch, has an adhesion of level 0, and a pencil hardness of 9H; (2) The low conductivity and high reflective glaze formed by the present invention can reflect visible light in the range of 400 to 2500 nm. It has high reflection of sunlight, solar infrared and ultraviolet rays, and the reflectivity of visible light is greater than 80%. It is also resistant to chemical corrosion, and has good thermal stability and dimensional stability. It is especially suitable for double-glass photovoltaic cell modules. (3) The low conductivity and high reflective glaze formed by the present invention is baked at a temperature of 680 to 720°C for 90 to 135 seconds. After tempering, the conductivity of the coating is ≤1×10 -4 (700℃), which prevents the glass from getting black spots during the anti-PID test. DETAILED DESCRIPTION
[0017] In order to further explain the present invention and the technical means and effects adopted to achieve the predetermined invention purpose, the present invention is described in detail below in conjunction with preferred embodiments: Example 1
[0018] A low-conductivity high-reflection glaze for a double-glass module photovoltaic glass back panel, wherein the raw material formula of the low-conductivity high-reflection glaze comprises the following weight percentages: 35wt% modified rutile, 45wt% glass binder, 18wt% quartz frit, 2wt% nano zirconium silicate, 21wt% varnish and 2% diluent.
[0019] The particle size of the low-conductivity and high-reflection glaze raw material is less than 8 μm.
[0020] The preparation process of the modified rutile is as follows: rutile titanium dioxide is prepared to a concentration of 200 g / L TiO 2 Take 200 ml of the uniformly dispersed suspension and transfer it to a beaker, then place it in a constant temperature heating mantle at 60°C and continue stirring and dispersing at 500 rpm for 30 min. 2 4g of silica sol with a content of 20% and a concentration of Al 2 O 3 6 g of aluminum sol with a content of 20% is added dropwise to the rutile titanium dioxide suspension at a constant feeding rate, and the mixture is stirred and dispersed continuously for homogenization. The feeding time is 60 min. After the feeding is completed, the mixture is aged for 24 h. After the aging, the mixture is stirred and dispersed for another 30 min, and then spray-dried at 450 °C and crushed by air flow to obtain modified rutile.
[0021] The chemical composition of the glass binder is Sb 2 O 3 2wt%,Na2 O 10wt%, K 2 O 2wt%, ZnO 15wt%, B 2 O 3 30wt%, SiO 2 35wt%, TiO 2 3wt%,Al 2 O 3 1wt%,BaO 2wt%,MgO 0wt%, SrO 0wt%,CaO 0wt%.
[0022] The particle size of the nano zirconium silicate is 400nm.
[0023] The varnish is composed of 3 wt % of polycaprolactone, 3 wt % of acrylic resin, 40 wt % of dipropylene glycol monomethyl ether, 53 wt % of tripropylene glycol monomethyl ether, 0.5 wt % of defoaming agent and 0.5 wt % of leveling agent in weight percentage.
[0024] The weight percentage composition of the diluent is: 1 wt % of water-based acrylic resin, 0.5 wt % of polycaprolactone, 0.5 wt % of fumed silica, and 98 wt % of diethylene glycol butyl ether.
[0025] The application method of the above-mentioned low-conductivity and high-reflection glaze is that the low-conductivity and high-reflection glaze is coated on the surface of the photovoltaic ultra-white glass backplane by screen printing, and baked at 720°C for 90s to obtain a low-conductivity and high-reflection double-glass module photovoltaic glass backplane.
[0026] The coating thickness of the low-conductivity and high-reflection glaze is 17 μm.
[0027] The low conductivity and high reflectivity double-glass photovoltaic glass back panel has a visible light reflectivity of 82.42% and a conductivity (700°C) of 1×10 -4 s / m, pencil hardness is 9H. Example 2
[0028] A low-conductivity high-reflection glaze for a double-glass module photovoltaic glass back panel, wherein the raw material formula of the low-conductivity high-reflection glaze comprises the following weight percentages: 35wt% of modified rutile, 43wt% of glass binder, 20wt% of quartz frit, 2wt% of nano zirconium silicate, 22wt% of varnish and 1% of diluent.
[0029] The particle size of the low-conductivity and high-reflection glaze raw material is less than 8 μm.
[0030] The preparation process of the modified rutile is as follows: rutile titanium dioxide is prepared to a concentration of 200 g / L TiO 2 Take 200 ml of the uniformly dispersed suspension and transfer it to a beaker, then place it in a constant temperature heating mantle at 60°C and continue stirring and dispersing at 500 rpm for 30 min. 2 4g of silica sol with a content of 20% and a concentration of Al 2 O 3 6 g of aluminum sol with a content of 20% is added dropwise to the rutile titanium dioxide suspension at a constant feeding rate, and the mixture is stirred and dispersed continuously for homogenization. The feeding time is 60 min. After the feeding is completed, the mixture is aged for 24 h. After the aging, the mixture is stirred and dispersed for another 30 min, and then spray-dried at 450 °C and crushed by air flow to obtain modified rutile.
[0031] The chemical composition of the glass binder is Sb 2 O 3 1wt%Na 2 O 9wt%, K 2 O 3wt%, ZnO 12wt%, B 2 O 3 35wt%, SiO 2 32wt%, TiO 2 3wt%,Al 2 O 3 1wt%,BaO 2wt%,MgO 0.5wt%, SrO 1wt%,CaO 0.5wt%.
[0032] The particle size of the nano zirconium silicate is 550nm.
[0033] The varnish is composed of 3 wt % of polycaprolactone, 3 wt % of acrylic resin, 40 wt % of dipropylene glycol monomethyl ether, 53 wt % of tripropylene glycol monomethyl ether, 0.5 wt % of defoaming agent and 0.5 wt % of leveling agent in weight percentage.
[0034] The weight percentage composition of the diluent is: 1 wt % of water-based acrylic resin, 0.5 wt % of polycaprolactone, 0.5 wt % of fumed silica, and 98 wt % of diethylene glycol butyl ether.
[0035] The application method of the above-mentioned low-conductivity and high-reflection glaze is that the low-conductivity and high-reflection glaze is coated on the surface of the photovoltaic ultra-white glass backplane by screen printing, and baked at 700°C for 110s to obtain a low-conductivity and high-reflection double-glass module photovoltaic glass backplane.
[0036] The coating thickness of the low-conductivity and high-reflection glaze is 21 μm.
[0037] The low conductivity and high reflectivity double-glass photovoltaic glass back panel has a visible light reflectivity of 82.46% and a conductivity (700°C) of 0.82×10 -4 s / m, pencil hardness is 9H. Example 3
[0038] A low-conductivity high-reflection glaze for a double-glass module photovoltaic glass back panel, wherein the raw material formula of the low-conductivity high-reflection glaze comprises the following weight percentages: 45wt% of modified rutile, 40wt% of glass binder, 10wt% of quartz frit, 5wt% of nano zirconium silicate, 18wt% of varnish, and 3% of diluent.
[0039] The particle size of the low-conductivity and high-reflection glaze raw material is less than 8 μm.
[0040] The preparation process of the modified rutile is as follows: rutile titanium dioxide is prepared to a concentration of 200 g / L TiO 2 Take 200 ml of the uniformly dispersed suspension and transfer it to a beaker, then place it in a constant temperature heating mantle at 60°C and continue stirring and dispersing at 500 rpm for 30 min. 2 4g of silica sol with a content of 20% and a concentration of Al 2 O 3 6 g of aluminum sol with a content of 20% is added dropwise to the rutile titanium dioxide suspension at a constant feeding rate, and the mixture is stirred and dispersed continuously for homogenization. The feeding time is 60 min. After the feeding is completed, the mixture is aged for 24 h. After the aging, the mixture is stirred and dispersed for another 30 min, and then spray-dried at 450 °C and crushed by air flow to obtain modified rutile.
[0041] The chemical composition of the glass binder is Sb 2 O 3 0wt%Na 2 O 7wt%, K 2 O 5wt%, ZnO 20wt%, B 2 O 3 23wt%,SiO 2 20wt%, TiO 2 5wt%,Al 2 O 3 3wt%,BaO 10wt%,MgO 2wt%, SrO 3wt%,CaO 2wt%.
[0042] The particle size of the nano zirconium silicate is 600nm.
[0043] The varnish is composed of 3 wt % of polycaprolactone, 3 wt % of acrylic resin, 40 wt % of dipropylene glycol monomethyl ether, 53 wt % of tripropylene glycol monomethyl ether, 0.5 wt % of defoaming agent and 0.5 wt % of leveling agent in weight percentage.
[0044] The weight percentage composition of the diluent is: 1 wt % of water-based acrylic resin, 0.5 wt % of polycaprolactone, 0.5 wt % of fumed silica, and 98 wt % of diethylene glycol butyl ether.
[0045] The application method of the above-mentioned low-conductivity and high-reflection glaze is that the low-conductivity and high-reflection glaze is coated on the surface of the photovoltaic ultra-white glass backplane by screen printing, and baked at 690°C for 120s to obtain a low-conductivity and high-reflection double-glass module photovoltaic glass backplane.
[0046] The coating thickness of the low-conductivity and high-reflection glaze is 15 μm.
[0047] The low conductivity and high reflectivity double-glass photovoltaic glass backplane has a visible light reflectivity of 82.18% and a conductivity (700°C) of 0.38×10 -4 s / m, pencil hardness is 9H. Example 4
[0048] A low-conductivity high-reflection glaze for a double-glass module photovoltaic glass back panel, wherein the raw material formula of the low-conductivity high-reflection glaze comprises the following weight percentages: 50wt% of modified rutile, 30wt% of glass binder, 19wt% of quartz frit, 1wt% of nano zirconium silicate, 22wt% of varnish, and 2% of diluent.
[0049] The particle size of the low-conductivity and high-reflection glaze raw material is less than 8 μm.
[0050] The preparation process of the modified rutile is as follows: rutile titanium dioxide is prepared to a concentration of 200 g / L TiO 2 Take 200 ml of the uniformly dispersed suspension and transfer it to a beaker, then place it in a constant temperature heating mantle at 60°C and continue stirring and dispersing at 500 rpm for 30 min. 2 4g of silica sol with a content of 20% and a concentration of Al 2 O 36 g of aluminum sol with a content of 20% is added dropwise to the rutile titanium dioxide suspension at a constant feeding rate, and the mixture is stirred and dispersed continuously for homogenization. The feeding time is 60 min. After the feeding is completed, the mixture is aged for 24 h. After the aging, the mixture is stirred and dispersed for another 30 min, and then spray-dried at 450 °C and crushed by air flow to obtain modified rutile.
[0051] The chemical composition of the glass binder is Sb 2 O 3 4wt%,Na 2 O 9wt%, K 2 O 2wt%, ZnO 3wt%, B 2 O 3 30wt%, SiO 2 30wt%, TiO 2 3wt%,Al 2 O 3 1wt%,BaO 5wt%,MgO 0wt%, SrO 11wt%, CaO 2wt%.
[0052] The particle size of the nano zirconium silicate is 480nm.
[0053] The varnish is composed of 3 wt % of polycaprolactone, 3 wt % of acrylic resin, 40 wt % of dipropylene glycol monomethyl ether, 53 wt % of tripropylene glycol monomethyl ether, 0.5 wt % of defoaming agent and 0.5 wt % of leveling agent in weight percentage.
[0054] The weight percentage composition of the diluent is: 1 wt % of water-based acrylic resin, 0.5 wt % of polycaprolactone, 0.5 wt % of fumed silica, and 98 wt % of diethylene glycol butyl ether.
[0055] The application method of the above-mentioned low-conductivity and high-reflection glaze is that the low-conductivity and high-reflection glaze is coated on the surface of the photovoltaic ultra-white glass backplane by screen printing, and baked at 680°C for 135s to obtain a low-conductivity and high-reflection double-glass module photovoltaic glass backplane.
[0056] The coating thickness of the low-conductivity and high-reflection glaze is 22 μm.
[0057] The low conductivity and high reflectivity double-glass photovoltaic glass back panel has a visible light reflectivity of 83.48% and a conductivity (700°C) of 0.32×10 -4 s / m, pencil hardness is 9H. Example 5
[0058] A low-conductivity high-reflection glaze for a double-glass module photovoltaic glass back panel, wherein the raw material formula of the low-conductivity high-reflection glaze comprises the following weight percentages: 42wt% of modified rutile, 45wt% of glass binder, 12wt% of quartz frit, 1wt% of nano zirconium silicate, 21wt% of varnish, and 1% of diluent.
[0059] The particle size of the low-conductivity and high-reflection glaze raw material is less than 8 μm.
[0060] The preparation process of the modified rutile is as follows: rutile titanium dioxide is prepared to a concentration of 200 g / L TiO 2 Take 200 ml of the uniformly dispersed suspension and transfer it to a beaker, then place it in a constant temperature heating mantle at 60°C and continue stirring and dispersing at 500 rpm for 30 min. 2 4g of silica sol with a content of 20% and a concentration of Al 2 O 3 6 g of aluminum sol with a content of 20% is added dropwise to the rutile titanium dioxide suspension at a constant feeding rate, and the mixture is stirred and dispersed continuously for homogenization. The feeding time is 60 min. After the feeding is completed, the mixture is aged for 24 h. After the aging, the mixture is stirred and dispersed for another 30 min, and then spray-dried at 450 °C and crushed by air flow to obtain modified rutile.
[0061] The chemical composition of the glass binder is Sb 2 O 3 2wt%,Na 2 O 7wt%, K 2 O 4wt%, ZnO 22wt%, B 2 O 3 23wt%,SiO 2 15wt%, TiO 2 5wt%,Al 2 O 3 3wt%,BaO 2wt%,MgO 2wt%, SrO 8wt%,CaO 7wt%.
[0062] The particle size of the nano zirconium silicate is 455nm.
[0063] The varnish is composed of 3 wt % of polycaprolactone, 3 wt % of acrylic resin, 40 wt % of dipropylene glycol monomethyl ether, 53 wt % of tripropylene glycol monomethyl ether, 0.5 wt % of defoaming agent and 0.5 wt % of leveling agent in weight percentage.
[0064] The weight percentage composition of the diluent is: 1 wt % of water-based acrylic resin, 0.5 wt % of polycaprolactone, 0.5 wt % of fumed silica, and 98 wt % of diethylene glycol butyl ether.
[0065] The application method of the above-mentioned low-conductivity and high-reflection glaze is that the low-conductivity and high-reflection glaze is coated on the surface of the photovoltaic ultra-white glass backplane by screen printing, and baked at 690°C for 135s to obtain a low-conductivity and high-reflection double-glass module photovoltaic glass backplane.
[0066] The coating thickness of the low-conductivity and high-reflection glaze is 24 μm.
[0067] The low conductivity and high reflection double glass photovoltaic glass back panel has a visible light reflectivity of 83.29% and a conductivity (700°C) of 0.43×10 -4 s / m, pencil hardness is 9H. Example 6
[0068] A low-conductivity high-reflection glaze for a double-glass module photovoltaic glass back panel, wherein the raw material formula of the low-conductivity high-reflection glaze comprises the following weight percentages: 40wt% of modified rutile, 45wt% of glass binder, 11wt% of quartz frit, 4wt% of nano zirconium silicate, 19wt% of varnish, and 3% of diluent.
[0069] The particle size of the low-conductivity and high-reflection glaze raw material is less than 8 μm.
[0070] The preparation process of the modified rutile is as follows: rutile titanium dioxide is prepared to a concentration of 200 g / L TiO 2 Take 200 ml of the uniformly dispersed suspension and transfer it to a beaker, then place it in a constant temperature heating mantle at 60°C and continue stirring and dispersing at 500 rpm for 30 min. 2 4g of silica sol with a content of 20% and a concentration of Al 2 O 3 6 g of aluminum sol with a content of 20% is added dropwise to the rutile titanium dioxide suspension at a constant feeding rate, and the mixture is stirred and dispersed continuously for homogenization. The feeding time is 60 min. After the feeding is completed, the mixture is aged for 24 h. After the aging, the mixture is stirred and dispersed for another 30 min, and then spray-dried at 450 °C and crushed by air flow to obtain modified rutile.
[0071] The chemical composition of the glass binder is Sb 2 O 3 2wt%,Na 2 O 8wt%, K 2 O 5wt%, ZnO 9wt%, B 2 O3 16wt%, SiO 2 29wt%, TiO 2 5wt%,Al 2 O 3 3wt%,BaO 2wt%,MgO 2wt%, SrO 8wt%, CaO11wt%.
[0072] The particle size of the nano zirconium silicate is 565nm.
[0073] The varnish is composed of 3 wt % of polycaprolactone, 3 wt % of acrylic resin, 40 wt % of dipropylene glycol monomethyl ether, 53 wt % of tripropylene glycol monomethyl ether, 0.5 wt % of defoaming agent and 0.5 wt % of leveling agent in weight percentage.
[0074] The weight percentage composition of the diluent is: 1 wt % of water-based acrylic resin, 0.5 wt % of polycaprolactone, 0.5 wt % of fumed silica, and 98 wt % of diethylene glycol butyl ether.
[0075] The application method of the above-mentioned low-conductivity and high-reflection glaze is that the low-conductivity and high-reflection glaze is coated on the surface of the photovoltaic ultra-white glass backplane by screen printing, and baked at 710°C for 100s to obtain a low-conductivity and high-reflection double-glass module photovoltaic glass backplane.
[0076] The coating thickness of the low-conductivity and high-reflection glaze is 24 μm.
[0077] The low conductivity and high reflectivity double-glass photovoltaic glass back panel has a visible light reflectivity of 83.62% and a conductivity (700°C) of 0.91×10 -4 s / m, pencil hardness is 9H.
[0078] The above visible light reflectivity is tested using an SMN-R fully intelligent reflectivity meter.
[0079] The above conductivity is tested using a DDS-307 digital conductivity meter.
[0080] The above pencil hardness is scored with a 9H pencil.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the principles and spirit of the present invention are included in the protection scope of the present invention.
Claims
1. A low conductivity, high reflective glaze for double-glass photovoltaic glass backplane, characterized in that: The raw material formula of the low-conductivity high-reflection glaze comprises the following weight percentages: 35-50wt% of modified rutile, 30-45wt% of glass binder, 10-20wt% of quartz frit, 1-5wt% of nano zirconium silicate, 18-24wt% of varnish, and 1-3% of diluent.
2. The low conductivity and high reflective glaze according to claim 1, characterized in that: The particle size of the low-conductivity and high-reflection glaze raw material is less than 8 μm.
3. The low conductivity and high reflective glaze according to claim 1, characterized in that: The modified rutile is prepared by encapsulating rutile titanium dioxide with 20 wt % Al2O3 aluminum sol and 20 wt % SiO2 silica sol.
4. The low conductivity and high reflective glaze according to claim 1, characterized in that: The chemical composition of the glass binder is Sb2O3 0-5wt%, Na2O 7-10wt%, K2O 2-5wt%, ZnO 3-22wt%, B2O316-35wt%, SiO2 15-35wt%, TiO2 3-5wt%, Al2O3 1-3wt%, BaO2-11wt%, MgO0-2wt%, SrO0-11wt%, and CaO0-11wt%.
5. The low conductivity and high reflective glaze according to claim 1, characterized in that: The particle size of the nano zirconium silicate is 400-600nm.
6. The low conductivity and high reflective glaze according to claim 1, characterized in that: The varnish is composed of 3 wt % of polycaprolactone, 3 wt % of acrylic resin, 40 wt % of dipropylene glycol monomethyl ether, 53 wt % of tripropylene glycol monomethyl ether, 0.5 wt % of defoaming agent and 0.5 wt % of leveling agent in weight percentage.
7. The low conductivity and high reflective glaze according to claim 1, characterized in that: The weight percentage composition of the diluent is: 1 wt % of water-based acrylic resin, 0.5 wt % of polycaprolactone, 0.5 wt % of fumed silica, and 98 wt % of diethylene glycol butyl ether.
8. The method for applying the low-conductivity high-reflection glaze according to claim 1, characterized in that: The low-conductivity high-reflection glaze is coated on the surface of the photovoltaic ultra-white glass backplane by screen printing, and baked at a temperature of 680-720° C. for 90-135 seconds to obtain a low-conductivity high-reflection double-glass module photovoltaic glass backplane.
9. The method for applying the low-conductivity high-reflection glaze according to claim 8, characterized in that: The coating thickness of the low-conductivity high-reflection glaze is 15-24 μm.
10. The method for applying the low-conductivity high-reflection glaze according to claim 8, characterized in that: The low conductivity and high reflection double glass photovoltaic glass back panel has a visible light reflectivity of 82.18-83.62% and a conductivity (700°C) of 0.32×10 -4 ~1×10 -4 s / m, pencil hardness is 9H.